2019
DOI: 10.46223/hcmcoujs.soci.en.9.2.261.2019
|View full text |Cite
|
Sign up to set email alerts
|

Four aspects of English speaking difficulties encountered by tertiary English-majored students

Abstract: Being able to speak English well is one of the outcomes for English training programs in different teaching and learning contexts. Nevertheless, there are many factors affecting the achievement of a high level of English speaking skills. One of these factors is derived from English speaking difficulties that ESL/EFL learners have to endure. This study, therefore, attempts to investigate the four aspects of speaking difficulties, namely affective, social, instructional and linguistic difficulties encountered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 3 publications
6
10
0
Order By: Relevance
“…Regarding their English proficiency levels, students started from an average perception in all skills: listening, reading, speaking and writing, with the last two being the lowest ones, and therefore the ones that need to be improved. Even though speaking is always the most difficult skill that students find, they do not practice enough due to practical difficulties, such as anxiety, embarrassment or mistake phobia [51]. The results obtained after the evaluation of the experience by the students indicate that the skill they claim they most improved is speaking.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding their English proficiency levels, students started from an average perception in all skills: listening, reading, speaking and writing, with the last two being the lowest ones, and therefore the ones that need to be improved. Even though speaking is always the most difficult skill that students find, they do not practice enough due to practical difficulties, such as anxiety, embarrassment or mistake phobia [51]. The results obtained after the evaluation of the experience by the students indicate that the skill they claim they most improved is speaking.…”
Section: Discussionmentioning
confidence: 96%
“…More support and opportunities to practice can help them overcome these obstacles. According to (Thao & Nguyet, 2019) most popular reasons that hinder EFL learners from speaking English well are the difficulties experinced by learners during their English speaking process. It is important to consistently practice and engage in various English speaking situations to get improvement in English speaking skills.…”
Section: Introductionmentioning
confidence: 99%
“…Successful English speaking is determined based on how accurately and fluently a speaker uses spoken language during a conversation (Brown & Lee, 2015;Dao, 2017;Manurung, 2015). However, Vietnamese undergraduates have faced difficulties in achieving English speaking skills due to insufficient proficiency, demotivating classroom environments, and limited exposure to English (Dao, 2017;Quyen et al, 2018;Thao & Nguyet, 2019). Similarly, Wang (2014) stated the situation in EFL classrooms where teachers likely spoke in mother tongue language and this situation limited students' English speaking as they did not have many opportunities speaking English in classrooms.…”
Section: Introductionmentioning
confidence: 99%
“…While artificial intelligence (AI) is a useable new technology for classrooms applications in terms of improving learners' speaking skills (Ali, 2020), little research has been conducted in Vietnam. Moreover, although the Vietnamese government has encouraged educators to utilise technology in the educational process , little research in Vietnam has suggested utilising a new technology like artificial intelligence technology to help students improve their English speaking skills (Dao, 2017;Quyen et al, 2018;Thao & Nguyet, 2019). Therefore, this study aimed to fill this gap by exploring the effects of an AI voice chatbot, an application of AI technology, on Vietnamese undergraduate students' English speaking skills.…”
Section: Introductionmentioning
confidence: 99%